2017
DOI: 10.1188/17.cjon.211-218
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Distress: Adult Acute Leukemia Survivors During and After Induction Therapy

Abstract: Self-reported distress was elevated for all groups. Highest distress scores were found during induction therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Early assessment and identification will enable targeted psychosocial and symptom interventions for younger survivors, ultimately improving HRQoL. 55,56 Our findings also support the potential benefits of adopting a biopsychosocial lens to the assessment and management of needs after treatment for hematological cancer, given the range of concerns identified by respondents in this sample. It is essential that nurses are equipped, trained, and educated to adequately address the survivorship concerns experienced by adults with hematological cancer.…”
Section: Limitationssupporting
confidence: 63%
See 1 more Smart Citation
“…Early assessment and identification will enable targeted psychosocial and symptom interventions for younger survivors, ultimately improving HRQoL. 55,56 Our findings also support the potential benefits of adopting a biopsychosocial lens to the assessment and management of needs after treatment for hematological cancer, given the range of concerns identified by respondents in this sample. It is essential that nurses are equipped, trained, and educated to adequately address the survivorship concerns experienced by adults with hematological cancer.…”
Section: Limitationssupporting
confidence: 63%
“…For example, younger hematological survivors are at greater risk for increased physical and psychosocial symptoms compared with older hematological survivors, as our data suggest. Early assessment and identification will enable targeted psychosocial and symptom interventions for younger survivors, ultimately improving HRQoL 55,56 …”
Section: Implications For Practicementioning
confidence: 99%
“…Different from a previous study, data at baseline in the current work were collected before participants accepting induction chemotherapy that resulted in lower depression prevalence. Another research has also shown that acute leukemia patients report the highest distress scores during induction chemotherapy 44 . Therefore, early psychological intervention to alleviate depression among patients with acute leukemia during induction chemotherapy was vital.…”
Section: Discussionmentioning
confidence: 99%
“…Another research has also shown that acute leukemia patients report the highest distress scores during induction chemotherapy. 44 Therefore, early psychological intervention to alleviate depression among patients with acute leukemia during induction chemotherapy was vital.…”
Section: Effect Of Vr-based Meditation On Depressionmentioning
confidence: 99%